Nikolai Gogol’s Literary Works, Tsar's Absolutism and Russian Cutural Life in the 19th Century: A Preliminary Note - Herdi Sahrasad; Muhammad Ridwan (Britain International of Linguistics Arts and Education (BIoLAE) Journal, 2019)
This paper is to study and understand the work of Nikolai Gogol, and to learn what and to what extent Tsar's absolutism in Russia under the old regime, has influenced his work, as well as its impact on the social, cultural, political, and economic realities of Russia under the Emperor's powerful rule in 19th century. Here also revealed, to what extent the tragic human life in Gogol's work and how the efforts of the author to uphold the existence and dignity of themselves and their society are revealed in the story "TarasBulba" and examine the tragic human life that experiences injustice and dehumanization, which is revealed in the story " Shinel " (Baju Mantelor Coat Dress). It is important to be able to learn and understand what and to what extent Gogol's role in the literary and cultural life of Russia in his day, especially regarding his influence in Russian literature and the values of Gogol's universal humanism for the life and culture of human being in this Earth.